Marine fuel efficiency for oil and gas offshore operation support activity by application of technology based speed control and contractor performance management - Alang Kelana; Audra Ligafinza; Machfud Machfud; Safri Saipullah; Suryaningsih Soedadi (Center for Science and Technology, IAIN Surakarta, 2018)
PHE ONWJ is an upstream oil and gas company engaged in the exploration and production of oil and gas. As a subsidiary of Pertamina Hulu Energy (PHE) under the PERTAMINA Group, PHE ONWJ operates within a working area of 8,300 km2, covering both offshore and onshore sites. In response to the decline in global oil prices, PHE ONWJ is required to reduce its operating costs, one of which is marine operations, which account for 10% of the total operating expenses, with 53% of this cost attributed to energy (fuel). The marine fuel efficiency program is a technology-based approach comprising a series of interconnected activities, including the determination of vessels’ economical speed, vessel control through the Fuel Monitoring System (FMS) and Vessel Tracking System (VTS), and improvement in contractor performance management. This program successfully reduced diesel fuel consumption by approximately 10,000 kiloliters, equivalent to a 34% reduction. Financially, it resulted in cost savings of Rp 80 billion and a reduction of 40 kilotons of CO2 emissions in 2016. The key success factors of this program include a strong commitment to implementing economical speed, fostering contractor partnerships, capacity building, and raising awareness to enhance contractor competence and behavior toward energy efficiency.